Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages of the need for raising the status of the midwife, and an effort on the part of the General Medical Council to improve the training in obstetrics of the medical students. This is all to the good, but we would urge on our Correspondents that there must be no diminution of effort. The maternal mortality rate remains at over 4 deaths per 1000 births. Some 3,000 mothers a year still die in childbirth. It would be deplorable if having helped to bring public attention to bear on this annual loss to the nation, as persistent as it is cruel, we for a moment relaxed our efforts. We know how great a proportion of these deaths is unnecessary; we can contrast such figures as those given in the Interim Report of the Departmental Committee on Maternal Mortality and Morbidity for certain great maternity hospitals, where the highest maternal mortality is 1.5 and the lowest well under 1 per 1000, with the black spots which report such figures as 9.90, 12.36 and 13.15. It is our duty to impress upon public opinion, during the time of stringency through which the nation is passing, that saving for the public purse is ill won at the cost of maternal life. We cannot close this Report without tribute to the voluntary nursing societies. For many years they have worked for the reduction of Maternal Mortality, and the following paragraph in the Annual Report of the Queen's Institute of District Nursing shows the value of such work:— "The Report received on the 66,003 midwifery cases attended by 811 Queen's Nurses and 2,926 Village Nurse-Midwives in England and Wales during 1930 showed a very good record. These cases represent approximately one-tenth of the total births in these counties. The maternal death rate for the cases undertaken by the Institute's midwives was 2 per 1000, which compares very favourably with the general rate of about 4 per 1000." (20) 292/824/1/58